Key correlates of exclusive breastfeeding at three timepoints: Evidence from Ethiopia. Issue 2 (14th September 2022) - Yigletu, Seblewongel; Tendulkar, Shalini A.; Holmes, Ashley C.; Abdelmenan, Semira; Tadesse, Amare; Berhane, Hanna Y.; Kosinski, Karen C.
Abstract: Aim: To compare factors associated with exclusive breastfeeding (EBF) within 1 h of birth, within 3 days, and within the first 6 months post‐birth. Methods: We used multivariate logistic regression models and data from "The Alive and Thrive Phase 2 Amhara Baseline Survey 2015" from Ethiopia ( N  = 3113). Results: Giving colostrum was strongly associated with EBF at all three time points, controlling for multiple confounders. Putting the baby to the breast before cleaning the baby and before cleaning the mother was significantly associated with EBF within 1 h and for the first 3 days. EBF within an hour of birth was more likely for girl babies than boy babies. Having a healthcare professional check whether the baby was sucking well was significantly associated with EBF 3 days post‐birth. Conclusions: The World Health Organization recommends breastfeeding within 1 h of birth and exclusively thereafter for 6 months, which can improve health outcomes for infants and children. In Ethiopia, many factors influence breastfeeding practices, but little is known about how these factors differ at various key timepoints in the 6 months after birth. Our study provides important information on correlates of EBF at three timepoints and shows that factors that are significantly correlated with EBF vary over time. Future research should assess the potential causal links among statistically significant associations between EBF and risk factors at various times between birth and 6 months of age. Ultimately, these findings have the potential to inform areas of intervention related to promoting EBF. Practitioner Points: Our models show that colostrum given at birth is strongly associated with whether mothers continue to exclusively breastfeed for 6 months, as recommended by the World Health Organization (WHO). We found that early breastfeeding supports are associated with exclusive breastfeeding for 3 days post‐birth. Supports such as having a healthcare provider check whether the baby was sucking well after birth and having assistance putting the baby to the breast before cleaning had positive effects on exclusive breastfeeding for the 3 days following birth. Given our own findings and the earlier work of others, breastfeeding support given at birth can be instrumental in improving the prevalence of exclusive breastfeeding. Interventions given at birth should be prioritised as the Ministry of Health in Ethiopia continues to develop and deliver comprehensive interventions to promote exclusive breastfeeding in rural regions of Ethiopia.